The Shame Is Not Mine: Addressing Abuse of Power Dynamics in Medical Training - Norman, Sierra (International Journal of Medical Students, 2024)
Medical student mistreatment is a longstanding issue that continues to occur far too often. This article narrates my experience with abuse of power dynamics in my medical training. Despite assurances from a site director that my concerns about a negative learning environment would not affect my evaluation and a text that I “finished strong,” he mistakenly sent me an email meant for a colleague, stating he believed I would be giving him a negative evaluation and that he would be failing me. In my evaluation, I was failed clinically with the comment: “it’s a matter of time before she hurts a patient.” The subsequent lack of action highlights the systemic vulnerability medical students face during their training. The article advocates for systemic changes, including institutional action to support their statements against mistreatment and retaliation, accountability for individuals perpetuating mistreatment, and supportive mental health resources. The article introduces A MATTER OF TIME, a project intended to support mental health and contribute to a more positive and compassionate generation of physicians.